LEGAL REGULATION OF FRANCHISING IN THE LEGISLATION OF FOREIGN COUNTRIES (World Bulletin of Management and Law, 2023)
The article discusses the concept and definition of a franchising agreement, its international legal regulation by various authoritative and popular organizations, as well as international legal acts. The international acts that exist today, the purpose of which is the legal regulation of franchising relations, are entirely advisory in nature, not having binding force for the subjects of these relations. Thus, at this time there is a need for unified international legal regulation of franchising relations, in other words, the creation of uniform rules for conducting franchising business